Advances in food security and sustainability. (Academic Press, 2018)
Advances in Food Security and Sustainability, Volume Three, takes a scientific look at the challenges, constraints and solutions necessary to maintain a healthy and accessible food supply in different communities. This ongoing series addresses a wide range of issues on food sustainability and security, exploring challenges related to protecting environmental resources while also meeting human nutritional requirements. Chapters included in this release include "A Food Systems perspective on food and nutrition security in Australia," "The potential, and limits, of agricultural intensification to improve the welfare of rural households in semi-arid areas," "Food supply chain fraud: the economic, environmental and social consequences" and much more. Contains expertise from leading contributions on the topics. Covers a vast array of subjects relating to food security and sustainability. Explores challenges related to protecting environmental resources while also meeting human nutritional requirements.